Analysis of the ŠKODA brand perceptions on different markets - Doležal, Jiří; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
Lately, brands are becoming increasingly important across all industries. Consumers are forming relationships with brands attributing brand building process a great significance. Automotive industry belongs to the most competitive industries with high brand loyalty attributing the brand even greater importance. This study focuses on a carmaker ŠKODA and perception of its brand between Czech, German and Finnish markets. In order to find the similarities and differences between the researched markets and provide future brand development, following objectives were set. First objective was to develop a theoretical framework integrating the brand equity components and the brand identity model on in-depth literature review, which serve as a basis for the empirical part. Second objective was to develop an overview regarding the branding benchmarks and current trends in the automotive industry. Thirdly, the objective was to analyze the three markets’ similarities and differences in brand perceptions of the case company ŠKODA based on the conducted survey and compare the results with previous studies. Lastly, based on the theory background, benchmarks, trends and conducted research, provide suggestions on how to improve brand perceptions of ŠKODA on researched markets. A quantitative research method, specifically an online questionnaire, has been chosen for this research. Total amount of 195 respondents from the three analyzed markets approached the questionnaire. However, not all respondents were admitted to participate in the research after the introductory question due to their possible influence on the findings which resulted in having 54 respondents from Czech Republic, 64 from Germany and 59 from Finland who fully completed the questionnaire. The research findings confirmed a strong position of ŠKODA brand on the Czech market, where perceptions predominantly surpassed the remaining markets.
The situation between the respondent’s perceptions in Germany and Finland was, however, not as evident. Previous studies already examined the brand perception of ŠKODA to some extent on the Czech market, however, no similar studies have been made on the markets of Germany and Finland. Therefore, this study compares the findings between individual researched markets as well as compares the findings with previous studies from Czech Republic. Despite different target groups, the results from previous studies on the Czech market were mostly in line with this study. A cross market comparison has been made with a study examining the brand perceptions of ŠKODA between United Kingdom and Poland. Common findings across markets and differences between genders have also been examined in this study. For further brand development, establishment of a car-sharing platform, communication of the vehicle connectivity features, communication through social media, consideration of subscription services and use of AR and VR technologies in connection with COVID-19 pandemic was advised with regard to the researched target group.
Vedoucí práce: Radek Čajka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses